Does food intake mediate the association between mindful eating and change in depressive symptoms?. Issue 9 (20th June 2020) - Winkens, LHH; Elstgeest, LEM; van Strien, T; Penninx, BWJH; Visser, M; Brouwer, IA
Abstract: Objective: To examine mediation by (i) diet quality and (ii) diet quantity in the associations of mindful eating domains with 3-year change in depressive symptoms. Design: Depressive symptoms were measured with the Center for Epidemiologic Studies Depression scale at baseline and 3-year follow-up. Four mindful eating domains (Focused Eating; Eating in response to Hunger and Satiety Cues; Eating with Awareness; Eating without Distraction) were measured with the Mindful Eating Behavior Scale. Food intake was measured with a 238-item FFQ. Diet quality was defined as the Mediterranean Diet Score (MDS). Diet quantity was defined as total energy intake (kcal/d; 1 kcal = 4·184 kJ). Mediation analyses with percentile-corrected bootstrap confidence intervals were conducted to calculate indirect effects. Setting: Longitudinal Aging Study Amsterdam. Participants: Adults aged 55 years or above ( n 929). Results: Diet quality (MDS) did not mediate associations of any of the four mindful eating domains with change in depressive symptoms. In contrast, total energy intake did mediate the associations with change in depressive symptoms for the mindful eating domains Eating with Awareness (indirect effects fully adjusted models: B = −0·014, 95 % CI −0·037, −0·002) and Eating without Distraction ( B = −0·013, 95 % CI −0·033, −0·001), but not for the other two domains. Post hoc multiple mediation analyses showed similar results. Conclusions: Higher scores on two mindful eating domains were associated with a decrease in depressive symptoms through lower total energy intake. Diet quantity, but not diet quality, could be a possible underlying mechanism in the associations between mindful eating and change in depressive symptoms.